Investigating the readiness of broadband continuous usage among rural dwellers in the northern region of Malaysia - Muraina, Ishola Dada; Sheik Osman, Wan Rozaini; Ahmad, Azizah (IACSIT Press, 2013)
Broadband is simply described as the transmission capacity that is faster than primary rate Integrated Services Digital Network at 1.5 or 2.0 megabits per second. Efforts have been made by the government of Malaysia to ensure that broadband should be seen as basic need and not a luxury.However, the internet users at the remote and rural areas in the world lack behind in using broadband which is always caused by lack of technology and economic factors, while the rural areas especially in the northern region of Malaysia are not excluded.This research investigated the readiness of rural dwellers in the northern region of Malaysia towards continuous usage of broadband by using a quantitative survey technique.The total numbers of 200 questionnaires were distributed to secondary school students that are residing in the rural areas of northern region of Malaysia.The results show that the rural dwellers are readily prepared for broadband continuous usage in their localization whenever they are sensitized towards it.